Promotional Advertising in an Augmented Reality Environment Using Audio Visual Approach for Trilogi University - Arifitama, Budi; Syahputra, Ade (IJTB (International Journal of Technology And Business), 2018)
Technology in the field of multimedia are often used as a promotional media campaign at the university. An element of multimedia is developed using the concept of audio and visual, where the delivery of transfer knowledge material with audio and visual models can provide a good understanding of the learning experience of the user. Nowadays, the ads circulating through various media channels have applied audio-visual techniques in promotional activities such as brochures, websites and promotional videos. Unfortunately, these type of promotional activities lacks value in terms of campus promotional innovation. Augmented reality technology comes as a solution to the stagnancy of promotional activities. The research method used is the audio-visual method as a development framework of augmented reality technology, this method is used by embedding audio and video features on augmented reality objects. Quantitative methods are used as a means of measuring the success of the development of augmented reality technology. The result of this research is to achieve an innovation of augmented reality technology development based on the framework designed to be used as a media for Trilogy University promotional campaign.